Induction of ovulation with pulsatile luteinising hormone releasing hormone. Issue 6412 (21st January 1984) - Mason, P; Adams, J; Morris, D V; Tucker, M; Price, J; Voulgaris, Z; Van der Spuy, Z M; Sutherland, I; Chambers, G R; White, S
Abstract : Ovulation was successfully induced with luteinising hormone releasing hormone in 28 women with hypothalamic amenorrhoea who had failed to respond to treatment with clomiphene. Luteinising hormone releasing hormone was administered in a pulsatile manner with miniaturised automatic infusion systems. The rate of ovarian follicular maturation, as monitored by serial pelvic ultrasonography, was similar to that observed in spontaneous cycles. Endocrine assessment by serial measurement of gonadotrophin, oestradiol, and progesterone concentrations showed hormone concentrations to be within the normal range. Intravenous treatment was required in only two patients, the remainder responding satisfactorily to subcutaneous infusion. All patients conceived within six cycles of treatment, and only one multiple pregnancy occurred.